Profil Berpikir Analitis Masalah Aljabar Siswa Ditinjau dari Gaya Kognitif Visualizer dan Verbalizer - Ilma, Rosidatul; Hamdani, A Saepul; Lailiyah, Siti (JURNAL REVIEW PEMBELAJARAN MATEMATIKA, 2017)
This research aimed to describe the profile of the visualizer and verbalizer students to think analytically in solving mathematical problems. The subjects were 3 visualizer students and 3 verbalizer students obtained by VVQ questionnaire. The research data are the form of analytical thinking tests and interviews were then analyzed based on the indicators of analytical thinking in solving mathematical problems based on the stage Polya. The results obtained by the visualizer students mention known and asked by picture, modelize problem by picture, use any different strategies, and conclude by picture. In other hand, verbalizer students mention known and asked by words, modelize problem by word (symbol or alphabet), use same strategy, and conclude by words. In the final result, there is no difference ability between the visualizer and verbalizer students cognitive style to think analytically in solving the problem because both are quite good.